2008
DOI: 10.1080/14992020802203322
|View full text |Cite
|
Sign up to set email alerts
|

Audiology education and practice from an international perspective

Abstract: This paper describes the international education and practice of audiology with the broader aim of proposing possible cost-effective and sustainable education models to address the current situation. Major audiology organizations worldwide were surveyed from February 2005 to May 2007, and organizations from 62 countries (78% of the world population) returned a completed survey. Overall, the results suggested a wide range of professionals providing hearing health care, and 86% of the respondents reported a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 9 publications
2
95
0
5
Order By: Relevance
“…Hearing health care surveys confirm that the paucity of services is in large part due to the limited numbers of available hearing health care professionals globally (Goulios & Patuzzi, 2008;Fagan & Jacobs, 2009). The average ratio of audiologists to the general population in developing countries reportedly varies between one for every half a million people to as high as one for every 6.25 million people.…”
Section: Inadequacy Of Global Hearing Health Care Servicesmentioning
confidence: 91%
See 1 more Smart Citation
“…Hearing health care surveys confirm that the paucity of services is in large part due to the limited numbers of available hearing health care professionals globally (Goulios & Patuzzi, 2008;Fagan & Jacobs, 2009). The average ratio of audiologists to the general population in developing countries reportedly varies between one for every half a million people to as high as one for every 6.25 million people.…”
Section: Inadequacy Of Global Hearing Health Care Servicesmentioning
confidence: 91%
“…In developed countries the average ratio for audiologists to people was one to every 20,000 (Goulios & Patuzzi, 2008). These shortages of hearing health care professionals are primarily due to a reported lack of government funding, professional and public awareness, and, most significantly, available training programs (Goulios & Patuzzi, 2008).…”
Section: Inadequacy Of Global Hearing Health Care Servicesmentioning
confidence: 99%
“…Unfortunately, there are limited prospects of identifying hearing loss in children, particularly within developing regions such as sub-Saharan Africa where an estimated 6.8 million children suffer from permanent disabling hearing loss [5,8,9]. This may be attributed to the absence of early hearing detection and identification (EHDI) programs due to reasons including limited human resources for ear and hearing care, a lack of appropriate equipment, costs and other health care priorities [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency is a global phenomenon -an analysis made with 62 countries has shown that 86% of them do not have enough professionals to meet their own needs 17 . This scenario is quite worrying considering that, at the same time, a combination of trends will result on a higher demand for SLP-Audiologists on the following decades: advances in medicine will entail higher life expectancy rates and therefore bring significant demographic changes such as population aging, meaning that the number of people with neurological and hearing disorders will tend to increase with time.…”
Section: Minimum Wages "I Would Like To Know That the Profession Of Smentioning
confidence: 99%